Noninvasive glucose monitoring using mid-infrared absorption spectroscopy based on a few wavenumbers - Kasahara, Ryosuke (Biomed Opt Express, 2017)
A method for performing noninvasive blood glucose measurements was developed. The method is based on mid-infrared absorption spectroscopy and uses only a few wavenumbers to measure blood glucose levels in vivo unconditionally. We found that the regression of blood glucose levels using only three wavenumbers, which were selected using a series cross-validation technique, realized accuracies comparable to those of cases in which a greater number of wavenumbers are used. In addition, we demonstrated the performance of this model through correlations among different types of data.